Social Networks and Health in Women: Results from a Qualitative Study in Iran - Baheiraei, Azam; Bakouei, Fatemeh; Mohammadi, Eesa (Current Women's Health Reviews, 2016)
Background: Social capital is a proposed social and contextual factor that affects health. Social capital is a combination of social networks and social cohesions developed in the given networks. In this conventional content analysis study, we explored the role of social networks in women’s health. Methods: Ten semi-structured, in-depth interviews of women (according on data saturation) were conducted in 2014. Transcripts of interviews were analyzed using inductive systematic thematic analysis and the themes were noted and summarized. Results: From analyzing the data, two themes were extracted including “feeling of self-efflorescence” and “health improvement”, by an emphasis on some effective strategies of social networks on health. Conclusions: Social networks can both directly and indirectly result in keeping and enhancing women’s health status. In this regard, feeling of self-efflorescence and health improvement were respectively the indirect and direct paths of the relationship between social networks and health.
Keywords: qualitative study